Quinic acid derivatives from Salicornia herbacea alleviate HMGB1-mediated endothelial dysfunction. (May 2015) - Tuan, Nguyen Q.; Lee, Wonhwa; Oh, Joonseok; Kwak, Soyoung; Lee, Hyun Gyu; Ferreira, Daneel; Bae, Jong-Sup; Na, MinKyun
Highlights: HMGB1 is a critical target for modulating vascular inflammatory responses. New caffeoylated quinic acids were isolated from Salicornia herbacea . The crude extract exhibited potent inhibition of HMGB1. Caffeoylated quinic acids alleviate HMGB1-mediated endothelial dysfunction. Caffeoyl quinic acids improved survival rates of CLP-induced septic in vivo models. Caffeoyl quinic acids can be commercialized as functional food components. Abstract: The high mobility group box 1 protein (HMGB1) has been targeted in the discovery of dietary supplements or medicinal resources to treat vascular inflammatory diseases. Salicornia herbacea has been utilized as a seasoned vegetable, salad, and traditional medicinal resource as well. Two new (1 and2 ) and four known (3 –6 ) caffeoylated quinic acids (CQAs) were isolated from the crude extract of S. herbacea exhibiting anti-HMGB1 activity. The isolated CQAs were further evaluated for their potential to ameliorate HMGB1-mediated vascular barrier disruption. Compounds1, 3, 5, and6 exerted vascular protective activity against HMGB1-induced inflammatory responses in both cellular and animal models and their mechanisms were also addressed. The active CQAs increased survival rates of cecal ligation and puncture-induced severe septic models to 20–40%. This study may serve the groundwork for commercializing CQAs as functional food components for prevention and treatment of pathogenic conditions related to endothelial hyperpermeability.